On the Design and Effectiveness of Targeted Expenditure Programs - Ahmad, Ehtisham (IMF Working Papers; Working Paper ;, 2004)
This paper argues that both horizontal and intertemporal competition among recipient governments are needed in order to ensure incentives for effective utilization of targeted transfers. This has implications for budgeting frameworks and the types of information needed that might be amenable to formal contracting between the levels of government.